Augmented single-unit muscle sympathetic nerve activity in heart failure with chronic atrial fibrillation - Ikeda, Tatsunori (Blackwell Science Inc, 2012)
NON-TECHNICAL SUMMARY: Augmentation of sympathetic nerve activity plays an important role in the deterioration of heart failure (HF). Atrial fibrillation (AF) is a well known and common complication in chronic HF. However, it remains unclear the relationship between sympathetic nerve activity and irregular ventricular rhythm induced by AF in HF. We examined the different sympathetic firing characteristics between HF patients with and without AF using a single-unit muscle sympathetic nerve activity (MSNA) method, which is a newly developed assessment of direct recording of sympathetic nerve activity. The firing frequency of single-unit MSNA was increased in HF patients with AF compared with HF patients without AF; particularly, those with a prolonged long RR interval showed multiple firings of single-unit MSNA. More intense single-unit MSNA within one cardiac interval occurred in HF patients with AF than patients without AF, even in AF patients receiving heart rate control therapy. Accordingly, our results suggest that AF per se augments central sympathetic activity and the restoration of sinus rhythm may be more effective in the treatment of HF patients with AF. ABSTRACT: Atrial fibrillation (AF) is a common complication in heart failure (HF) patients. However, it remains unclear whether irregular ventricular response patterns induced by AF increase sympathetic nerve activity. We measured resting multi- and single-unit muscle sympathetic nerve activity (MSNA) in 21 age-matched HF patients with chronic AF (n= 11) rhythm or sinus rhythm (SR, n= 10). The multi-unit MSNA, which was expressed as total activity, was similar between HF + AF patients and HF + SR patients. However, the single-unit MSNA in HF + AF patients was significantly greater than that in HF + SR patients (62 ± 9 spikes min(−1)vs. 42 ± 4 spikes min(−1), P < 0.05). Moreover, the incidence of multiple firing of single-unit MSNA within a given burst was augmented in HF + AF patients as compared with HF + SR patients (48 ± 8%vs. 26 ± 3%, P < 0.01). A significant negative relationship was observed between the reduced diastolic pressure induced by a prolonged cardiac interval in AF subjects and single-unit MSNA frequency within one cardiac interval in each HF + AF subject. The firing characteristics of single-unit MSNA were different between HF patients with AF and HF patients with SR; particularly, those with a prolonged long RR interval showed multiple firings of single-unit MSNA. These findings suggest that AF per se leads to the instantaneous augmentation of single-unit MSNA induced by decreased diastolic pressure, which might partially contribute to disease progression in HF patients.